(untitled) (The Review of Diabetic Studies, 2024)
Infectious illnesses among patients with multimorbidity create numerous difficulties in terms of therapeutic choices due to the pathophysiological changes, polypharmacy and increased susceptibility to adverse drug effects. With the world becoming older with the population, and the proliferation of chronic non communicable disease, the number of patients who require complex series of medication, whilst they are being managed against acute or chronic infection has also risen. Multimorbidity is also multifaceted, which frequently results in polypharmacy, which in turn adds to the risk of drug-drug and drug-disease interactions and medication non adherence, as well as cumulative organ toxicity which mainly causes renal and hepatic dysfunction. Aging-induced pharmacodynamic and pharmacokinetic alterations, such as immunosenescence and frailty complicate antimicrobial choice and dosing and therefore the therapeutic index between efficacy and toxicity. Nevertheless, this incorrect antimicrobial dosing within such a group can result in subtherapeutic exposure that will moderate the cultivation of antimicrobial resistance or supratherapeutic exposure that triggers severe adverse events. Large fraction of infections necessitating hospitalization are in patients harboring multimorbidity and taking complicated polypharmacy regimens, which increases emerging risks of pharmacotherapy that may be addressed by the centrality of the clinical pharmacist in practice as explained in this review. Clinical pharmacy interventions of critical importance include regimented medication review, therapeutic drug monitoring, deprescribing practice, compliance facilitation, risk stratification, and tailored antimicrobial therapy according to individualized patient determinants such as renal function, frailty, and comorbidity burden. There is strong evidence showing that pharmacist led interventions reduce drug related problems, adverse drug events, inappropriate polypharmacy and healthcare utilization and improve clinical outcomes. There is also an opportunity to use new complementary tools, such as: pharmacogenomic-guided therapy, digital and general health technologies, and clinical decision support systems, to guide therapeutic optimization in this particularly vulnerable group. In aggregate, clinical pharmacy services are critical to optimizing safe, effective, and patient centered infectious disease management for people with multimorbidity and complex medication regimens.